The Effect Of Investment Decisions, Funding Decisions And Dividend Policy On Firm Value In The Banking Industry Listed On The Bei For The Period 2021-2023: - Nasrudin, Nasrudin (Dinasti Publisher, 2023)
This research aims to determine the influence of investment decisions, funding decisions and dividend policies in the banking industry listed on the IDX for the 2021-2023 period. By using samples using purposive sampling techniques from 10 companies and multiple regression analysis, the research results show that investment decisions have a positive impact and have a significant effect on company value, while funding decisions and dividend policies do not have a significant effect on company value. In this study, researchers suggest that companies and managers pay attention to important decisions within the company to increase company value.